Laporan Kasus : Ulkus Kornea Okuli Sinistra dengan Impending Perforasi - Pabiola, Dea Okta; Maulana, Muhammad (CV. Jasa Sukses Abadi, 2026)
Corneal ulcer is the partial loss of the corneal surface due to the death of corneal tissue, characterized by the presence of a purulent infiltrate accompanied by a corneal defect extending from the epithelium to the stroma. Corneal ulcers can occur due to trauma from foreign objects, tear insufficiency, or diseases that facilitate the entry of bacteria, viruses, or fungi into the cornea. Appropriate medical management to prevent complications such as endophthalmitis, cataracts, secondary glaucoma, and corneal perforation. A man was reported with complaints of blurred vision in his left eye accompanied by pain, itching, and watering since 1 month before admission to the hospital. The complaint is exacerbated by the presence of white spots in the left eye and a sharp decline in vision, with the patient only able to see shadows from a close distance. Examination of the left eye revealed a visual acuity of 1/300, with the eyeball in an orthophoric position. Inspection of the upper and lower eyelids revealed edema, hyperemia, and discharge. The ball movement is good, but the field of view is difficult to assess. The cornea has ulcers that are diffuse, extending from the center to the periphery, 1 mm from the limbus, with irregular, round borders and a size of 5 mm. The anterior chamber, iris, pupil, lens, and fundus examination are difficult to assess. The patient was diagnosed with a left eye corneal ulcer with impending perforation.